2017
DOI: 10.1002/ijc.31046
|View full text |Cite
|
Sign up to set email alerts
|

Red and processed meat intake and cancer risk: Results from the prospective NutriNet‐Santé cohort study

Abstract: The International Agency for Research on Cancer (WHO-IARC) classified red meat and processed meat as probably carcinogenic and carcinogenic for humans, respectively. These conclusions were mainly based on studies concerning colorectal cancer, but scientific evidence is still limited for other cancer locations. In this study, we investigated the prospective associations between red and processed meat intakes and overall, breast, and prostate cancer risk. This prospective study included 61,476 men and women of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 38 publications
8
101
0
2
Order By: Relevance
“…We should consider that there are no nutritional disadvantages to avoiding red meat. The International Agency for Research on Cancer (WHO‐IARC) suggests limiting the consumption of red meat, primarily due to its association with some cancers, and classified red meat and processed meat as probably carcinogenic and carcinogenic for humans, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should consider that there are no nutritional disadvantages to avoiding red meat. The International Agency for Research on Cancer (WHO‐IARC) suggests limiting the consumption of red meat, primarily due to its association with some cancers, and classified red meat and processed meat as probably carcinogenic and carcinogenic for humans, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…suggests limiting the consumption of red meat, primarily due to its association with some cancers, 40 and classified red meat and processed meat as probably carcinogenic and carcinogenic for humans, respectively.…”
Section: F I G U R E 1 Theoretical Model and Framework Of Sem Analysismentioning
confidence: 99%
“…The classification of unprocessed red meat as carcinogens has stirred up huge debates among research communities. Cohort studies have found positive associations between unprocessed red meat and many cancers, although these results are inconsistent except for colorectal cancer . Likewise, no consistent findings have been found on the associations between unprocessed red meat and cardiovascular disease and diabetes .…”
Section: Introductionmentioning
confidence: 95%
“…Cohort studies have found positive associations between unprocessed red meat and many cancers, although these results are inconsistent except for colorectal cancer. [1][2][3][4][5][6][7] Likewise, no consistent findings have been found on the associations between unprocessed red meat and cardiovascular disease and diabetes. [8][9][10][11][12] Recently, even the weak association between unprocessed red meat and colorectal cancer was called into question.…”
Section: Introductionmentioning
confidence: 97%
“…Similar findings were reported in the UK (Anderson et al, 2018[2]). In a prospective study, Diallo et al (2018[9]) found that high intake of red and processed meat was associated with a higher risk of overall cancers and breast cancer. In addition, increased intake of red and processed meat was found to be positively linked to a higher risk of chronic obstructive pulmonary disease (Salari-Moghaddam et al, 2018[24]).…”
mentioning
confidence: 99%